MATHEMATICAL MODELING OF A TECHNICAL OBJECT DEPENDENT FAILURES - Bosov, A. A.; Hryshechkina, T. S.; Savchenko, L. M. (Science and Transport Progress, 2009)
Dependent failure models of technical objects on the basis of wave approach are suggested.